DAMPAK SOSIAL DAN EKONOMI KEBERADAAN OBJEK WISATA (STUDI KASUS THE UNIQUE PART WATERBOOM) DI KENAGARIAN MUARO KALABAN KOTA SAWAHLUNTO - Destaria, Lisa; Fachrina, Fachrina; Yasin, Faishal (Pendidikan Sosiologi, 2013)
Establishment of tourism development in an area can improve peoples lives, because of the many available jobs and could open up new ventures, associated with reality in lapanagan in the know that the founding attraction Waterboom Muaro Kalaban social and economic impacts after the waterboom. The purpose of this study is to describe how social and economic impacts after the waterboom attractions in the Village District Muaro Kalaban Silungkang Sawahlunto.This study used a qualitative approach and descriptive bertipekan, collecting data by interviewing multiple informants are people and community leaders such as village head Muaro Kalaban, Head of Dusun Sawah Mine, merchants around waterboom and in the parking area and the existing waterboom around objects waterboom tour. No informant Pemeilihan this study using purposive sampling technique. Types of data used are primary data and secondary data. Method of data collection was done in three ways (1) observation, (2) in-depth interviews, and (3) documentation. The unit of analysis is the group. Used data analysis is divided into three, namely (1) data reduction, (2) The presentation of the data, and (3) Conclusion.The results revealed that after the founding of attraction Waterboom Muaro Kalaban social and economic impacts. Social impacts arising divided into two, namely positive and negative impacts, while the negative impact that imitate the dress and behavior of swimming, religious values people have started to fade. While the positive impact of increased education and better relations interaction. Economic impacts arising that is the creation of jobs for the people, rising incomes, a community initiative ntuk build shophouses, increased facilities and infrastructure such as roads.